THE BENEFITS OF ELDERLY GYMNASTICS ON CHOLESTEROL LEVELS AT KAWAN SEIRING POSYANDU IN BAMBU KUNING VILLAGE, WORKING AREA OF PUSKESMAS REJOSARI - Mutiara, Sherly; Situmorang, Masriani; Tonis, Marian; Claudyana, Inka Desla (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2024)
Elderly gymnastics is a series of regular, directed, and planned movements performed with the aim of enhancing the functional abilities of the body. Regular elderly gymnastics can lower blood cholesterol levels in the elderly. If cholesterol levels decrease, it is highly beneficial for the body as it can reduce the risk of cardiovascular diseases. The objective of this community service implementation is to lower cholesterol levels among the elderly at the Kawan Seiring Posyandu in the Bambu Kuning Village within the working area of Puskesmas Rejosari in 2024. The method of community service implementation involves providing education and active physical activities through elderly gymnastics. There were 10 elderly participants in this community service activity. The results of this service activity show differences in cholesterol levels before and after gymnastics among the elderly, as elderly gymnastics are highly beneficial for human health, including improving the function of the heart, lungs, and blood vessels.